A randomized trial on haemodynamic changes during intubation using airtraqr and macintosh laryngoscope - Chen, Chua Chen (2013)
Sympathetic response is associated with laryngoscopy and intubation. Such response can be hazardous to patients with poor physiological reserve. Many research and development were done to look for the best way of obtunding this response. New laryngoscopes like Airtraq® laryngoscope were designed to improve the process of intubation and thus reduces sympathetic response secondary to laryngoscopy and intubation. To compare the sympathetic response and immediate complication of endotracheal intubation using Airtraq® and Macintosh laryngoscope, which are then analyzed to determine if the newer Airtraq® laryngoscope is an inferior, equal or superior alternative to the mainstay Macintosh laryngoscope. This is an experimental, prospective, stratified, single blind randomized study. 142 patients who had fulfilled the inclusion and exclusion criteria were allocated into Airtraq® and Macintosh group according to age group, 18-29, 30-39, 40-49 and 50-59. sBP, dBP, MAP and HR of patients at baseline, during intubation, 1, 2, 3, 4, and 5 minutes post-intubation were collected and compared. Complications associated with laryngoscopy and intubation were observed in this study too. Statistical analysis using mean (SD) and ANOVA test were performed on the data obtained. Data was compared in general, age group below 40 years old and age group above 40 years old. In general, there was significant difference within group for both Airtraq® and Macintosh groups for sBP, dBP, MAP (p < 0.001). However, there was no significant different between and within-between group for sBP, dBP, MAP and HR. Pressure response was significant different within and between groups for age group more than 40 years old (p 0.05) and the changes were more than 20.0% from the baseline in Airtraq® group. No significant different in HR between 2 groups and the changes were less than 20.0% in all age groups. Airtraq® laryngoscope causes less sympathetic stimulation during laryngoscopy and intubation. It is suitable to use in elder patients and those which exaggerated sympathetic response during laryngoscopy can be hazardous.